The Effect of Employer Branding and Corporate Social Responsibility on Intention to Apply for Jobs in Start-Up Companies: The Mediating Role of Corporate Reputation - Muhammad Fauzi Khoirul Mz; Jati Waskito (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study investigates the effects of employer branding and corporate social responsibility (CSR) on job application intentions toward start-up companies, with corporate reputation as a mediating variable. The research adopts a quantitative explanatory method, utilizing survey data from 150 Management students at Universitas Muhammadiyah Surakarta's Faculty of Economics and Business. Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method was used to examine the data. The findings show that employer branding and CSR have positive and significant effects on job application intention. Furthermore, employer branding and CSR significantly impact a company's reputation, which, in turn, positively affects job application intention. The mediation study demonstrates that a company's reputation partially mediates the relationships between employer branding and job application intention, as well as between job application intention and CSR. These findings highlight the strategic importance of strengthening employer branding, implementing consistent CSR practices, and building a favorable company reputation to attract potential applicants, particularly in start-up companies.